The Spectra of Unstressed Vowels in Standard Lithuanian - Kaukėnienė, Lidija (Kalbotyra, 2002)
The article analyses the spectra of unstressed vowels in Standard Lithuanian, their acoustic and articulation characteristics. The unstressed vowels are compared with the stressed ones.The results of the experiment have demonstrated that there are no big acoustic differences between the first and the second before stress-situated vowels and between the first and the second after stress standing vowels. All before stress and after stress-situated variants have similar shifts.The low rise vowels [a.], [e.] have the biggest qualitative reduction. The high rise vowel [u] has the smallest qualitative reduction.The unstressed compact vowels are less compact than the stressed ones, the diffuse vowels are less diffused. The timbre of low unstressed vowels is higher (except the vowel [a]) than the stressed ones. The timbre of high vowels (except the vowel (e.]) is lower than the stressed ones. The unstressed open vowels are closer, the unstressed close vowels opener than the stressed ones. It means that unstressed Lithuanian Standard vowels do not have utmost front, back, high and low articulation – they are focusing in the centre of the spectra. The short vowels after the stress have a more noticeable qualitative reduction than the ones found before the stress. The long vowels found before stress have a clearer qualitative reduction than the ones after the stress.